2020
DOI: 10.1371/journal.pone.0242598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma anti-GPL-core IgA and IgG for diagnosis of disseminated non-tuberculous mycobacteria infection

Abstract: Detection of IgA antibody against Mycobacterium avium complex (MAC) glycopeptidolipid (GPL) has recently been shown to improve the diagnosis of MAC pulmonary disease but has yet to be tested in disseminated Non-tuberculous mycobacteria (NTM) infection. In this study, we address the diagnostic efficacies of an anti-GPL-core ELISA kit in disseminated lymphadenopathy patients positive for NTM culture and anti-IFN-γ autoantibodies. The study was conducted in a tertiary referral center in northeastern Thailand and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…We also showed that the median time required for the second positive sputum culture was 51 days in our cohort, suggesting the time, cost, and effort-saving effect of using single culture isolation plus anti-GPL-core IgA antibody as another diagnostic criterion. Although the specificity of anti-GPL-core IgA antibodies has been reported to be different between countries ( 7 , 10 , 12 14 ), it is still high in many countries. Therefore, we propose adding single culture isolation plus anti-GPL-core IgA antibody as “combined microbiological and serological criteria” to the diagnostic guidelines for MAC-PD and MAB-PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also showed that the median time required for the second positive sputum culture was 51 days in our cohort, suggesting the time, cost, and effort-saving effect of using single culture isolation plus anti-GPL-core IgA antibody as another diagnostic criterion. Although the specificity of anti-GPL-core IgA antibodies has been reported to be different between countries ( 7 , 10 , 12 14 ), it is still high in many countries. Therefore, we propose adding single culture isolation plus anti-GPL-core IgA antibody as “combined microbiological and serological criteria” to the diagnostic guidelines for MAC-PD and MAB-PD.…”
Section: Discussionmentioning
confidence: 99%
“…This was a single referral center study, and the participants were all Japanese. Although the positive rate of anti-GPL-core IgA antibodies among healthy individuals is very low in Japan, the USA, and Taiwan ( 7 , 12 , 14 ), it was reported to be quite high in Thailand ( 10 ). The high positive rate of anti-GPL-core IgA antibody among healthy individuals might affect the PPV of single culture isolation plus anti-GPL-core IgA antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among bacterial infections, the IgA response has been investigated in infections caused by Bordetella pertussis ( 3 ), Chlamydia trachomatis , and mycobacteria, and especially Mycobacterium tuberculosis , with about three quarters of all IgA studies concerning this pathogen within the Mycobacterium genus ( 4 8 ). Other mycobacterial infections targeted in IgA serological studies, especially in cystic fibrosis (CF) patients, were Mycobacterium avium ( 9 ) or M. abscessus ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%